Model of Rice Stock Estimation - Dadang Sukandar (Media Gizi dan Keluarga, 2000)
The objective of this study was to develope model of rice stock estimation and the derivation. Rice stock was defined as summation of last stock plus rice delta, where rice delta defined as a linear function of production, consumption, export, import and some correction factors. There were four significant result of this study i.e : 1) recursive model of rice stock estimation, 2) model of rice stock adequacy with respect to population rice consumption and 3) model of rice stock forcasting. From model testing trough the use of rice data 1995 – 1997 of west Java, it can be concluded that model can give good rice stock estimation.